Leadership and Communication, Fundamental Competences for a Project Director - Idrobo-Dávalos, Paul (2018)
This article analyzes the importance of leadership and communication in the role of the project manager. For this purpose, it is discussed the incidence of these competencies at the management levels, their characteristics and implications in the role of the project manager are identified, and some nuances with which they are presented in Latin America are distinguished. The literature reviewed shows that the behavior of the project manager associated with leadership and communication is crucial to ensure management effectiveness and, in addition, significantly affect the success of the project. It is concluded, therefore, that the development of these competences should be encouraged in the directors, as well as the ability to adapt them according to the context in which the project is executed.